The effect of naturally acquired rumen fluke infection on animal health and production in dairy and beef cattle in the UK - Atcheson, Erwan; Lagan, Bernard; McCormick, Ross; Edgar, Hilary; Hanna, Robert E. B.; Rutherford, Naomi H.; McEvoy, Amanda; Huson, Kathryn M.; Gordon, Alan; Aubry, Aurelie; Vickers, Mary; Robinson, Mark W.; et al. (Frontiers in Veterinary Science, 2022)
The incidence of paramphistomosis, caused by the rumen fluke, Calicophoron daubneyi, has greatly increased within Europe in the last 15-20 years. However, the production impacts of this disease are poorly understood. This study firstly aimed to investigate the prevalence of rumen fluke in England and Northern Ireland (NI) by conducting an abattoir survey of dairy and beef cattle which also allowed the impact of rumen fluke on carcass weight, conformation and fat classification to be assessed. Secondly, an experiment aimed to assess the impact of C. daubneyi infection on diarrhoea score, production loss and welfare in dairy heifers, while also evaluating the impacts of treating infected heifers with oxyclozanide. Rumen fluke prevalence was greater in NI than in England, with 53.8% (95% CI 51.9 - 55.9%) of the NI cattle carcases sampled being infected compared to 16.3% (95% CI 15.8 - 16.8%) and 17.9% (95% CI 17.4 - 18.4%) detected at the two abattoirs in England. However, there was no significant difference (P>0.05) in the cold carcass weight between infected and non-infected cattle. Similarly, carcass conformation and fat classification were unaffected (P>0.05) by the presence of rumen fluke. In the second experiment, daily live weight gain (DLWG), diarrhoea score and welfare score were also unaffected (P>0.05) by rumen fluke infection and by oxyclozanide treatment against rumen fluke. The farms in this experiment were managed to a high standard and animals had no intercurrent disease. Therefore, these findings suggest that on well managed farms, production losses (growth rates) should not be compromised as a result of sub-clinical rumen fluke infection.